2013
DOI: 10.1007/s00192-013-2104-0
|View full text |Cite
|
Sign up to set email alerts
|

Urinary nerve growth factor: a biomarker of detrusor overactivity? A systematic review

Abstract: Nerve growth factor (NGF) is a signalling protein that interacts with specific receptors in autocrine, paracrine and endocrine modes. It is produced by bladder smooth muscle and urothelium. Patients with overactive bladder and detrusor overactivity (DO) have been found to have increased urinary NGF levels in several small studies. The objective of the review was to assess the accuracy of NGF as a biomarker in the diagnosis of DO by a systematic review of the literature. A systematic search of MEDLINE, Embase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…NGF and ATP are representative and useful urinary biomarkers for OAB. 13,14 These factors are produced from bladder smooth muscle and urothelium. In fact, anticholinergic drugs for OAB reduce their urinary levels, which are produced from these tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NGF and ATP are representative and useful urinary biomarkers for OAB. 13,14 These factors are produced from bladder smooth muscle and urothelium. In fact, anticholinergic drugs for OAB reduce their urinary levels, which are produced from these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Several investigators have reported that anticholinergic drug treatment for non-neurogenic OAB reduced the levels of these OAB-related urinary biomarkers. 15,16 However, relationships between LUT dysfunction, including OAB symptoms as a result of HAM/ TSP, and these urinary biomarkers are still not reported.…”
mentioning
confidence: 99%
“…To overcome this problem, a biomarker is needed to differentiate between the two diseases. Rachaneni et al [37] discussed whether urinary NGF could serve as a biomarker of detrusor overactivity (DO) in patients with OAB. DO, which is defined as detrusor contractions during urodynamics, is responsible for symptoms in most OAB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Near infrared spectroscopy has also been shown to be an unreliable method for detecting DO in women with OAB symptoms [31]. While several small studies have demonstrated a trend towards higher urinary nerve growth factor (NGF) in patients with DO, a recent systematic review of the literature has stated that the data are imprecise and hence NGF cannot be recommended for use in current clinical practice [32].…”
Section: Commentmentioning
confidence: 99%